Estudio de aplicabilidad de material biocompuesto con fibra de cascarilla de arroz para la fabricación de engranajes de diente recto para aplicaciones de baja carga (2021)
The project is based on studying the application of biocomposite material with rice husk (CA) for the manufacture of flat tooth gears for low power transmission systems; This idea arises from the need to find different alternatives to the metal and plastic gears used in the industry. Power transmission systems are designed mainly with flat tooth metal gears, characterized by being heavy, expensive to manufacture, difficult to machine, very noisy and require constant lubrication, therefore it is necessary to study design alternatives for these mechanical systems. The objective of the project is to develop a straight tooth gear, using biocomposite material of AC fiber and polymeric matrix, to demonstrate the applicability according to its mechanical characteristics; developing the project under a descriptive field and applied research, where the design and manufacturing parameters for the gears to be studied will be defined, to later carry out mechanical resistance tests and obtain quantitative data with which to define the probable applications for material gears compound. An easy machining type of MC-based gear was obtained, applicable to power transmissions with torques less than 15 . The limes could be applied as substitutes for metal and plastic gears in low-power transmission applications.